2022
DOI: 10.3390/ijms231911063
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cerebrospinal Fluid Proteins and Albumin Determine a Poor Prognosis for Spinal Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a heterogeneous disease, both in its onset phenotype and in its rate of progression. The aim of this study was to establish whether the dysfunction of the blood–brain barrier (BBB) and blood–spinal cord barrier (BSCB) measured through cerebrospinal fluid (CSF) proteins and the albumin-quotient (QAlb) are related to the speed of disease progression. An amount of 246 patients diagnosed with ALS were included. CSF and serum samples were determined biochemically for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Despite its limitations, the albumin quotient (QAlb) is the most commonly used marker for reflecting BBB/BSCB permeability. Elevation in QAlb levels has been reported in 20–50% of ALS patients [ 17 , 18 , 19 ] and its association with the progression of the disease remains controversial [ 18 , 20 , 21 , 22 ]. Moreover, BBB/BSCB impairments have especially been studied in the context of SOD1 mutated models of the disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its limitations, the albumin quotient (QAlb) is the most commonly used marker for reflecting BBB/BSCB permeability. Elevation in QAlb levels has been reported in 20–50% of ALS patients [ 17 , 18 , 19 ] and its association with the progression of the disease remains controversial [ 18 , 20 , 21 , 22 ]. Moreover, BBB/BSCB impairments have especially been studied in the context of SOD1 mutated models of the disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study show that increased BBBp, which is associated with vascular risk factors and CVB, is independently associated with a worse prognosis in individuals with cognitive decline. QAlb has been associated with a poorer prognosis in other neurological diseases such as spinal amyotrophic lateral sclerosis or multiple sclerosis 60,61 . To the best of our knowledge, this is the first time that QAlb has been related to the progression of cognitive decline.…”
Section: Discussionmentioning
confidence: 78%
“…QAlb has been associated with a poorer prognosis in other neurological diseases such as spinal amyotrophic lateral sclerosis or multiple sclerosis. 60 , 61 To the best of our knowledge, this is the first time that QAlb has been related to the progression of cognitive decline. Moreover, the association between increased BBBp and clinical progression was observed independently of b‐AD.…”
Section: Discussionmentioning
confidence: 85%
“…The research of biomarkers in cerebrospinal fluid (CSF) is one of the most active areas of ALS. Most previous studies focused on comparing the differences between healthy controls (HCs) and ALS patients, and most found that CSF IgG levels, CSF protein levels, and the quotient of CSF albumin and blood albumin (Q ALB ) in ALS patients were higher than those in controls ( Gårde et al, 1971 ; Leonardi et al, 1984 ; Norris et al, 1993 ; Assialioui et al, 2022 ). However, the associations between CSF profiles and the disease phenotype of ALS are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the associations with the disease phenotypes such as the stage of the disease or the progression rate turned out to be unapparent in the majority of the studies ( Tarasiuk et al, 2012 ; Zhao et al, 2020 ). One recent study found CSF protein was significantly negatively associated with the ALS functional rating scale revised (ALSFRS-R) scores in female ALS, not in male ALS ( Assialioui et al, 2022 ). These inconsistent findings of the CSF profiles may result from inherent limitations, including small sample size, varied applied methods, characteristics of enrolled ALS patients, ethnic differences of participants, and so on.…”
Section: Introductionmentioning
confidence: 99%